Clinical and Functional Features of Epilepsy-Associated In-Frame Deletion Variants in SCN1A - Wang, Jing-Yang; Tang, Bin; Sheng, Wen-Xiang; Hua, Li-Dong; Zeng, Yang; Fan, Cui-Xia; Deng, Wei-Yi; Gao, Mei-Mei; Zhu, Wei-Wen; He, Na; Su, Tao (Frontiers in Molecular Neuroscience, 2022)
Objective: Naturally occurring in-frame deletion is a unique type of genetic variations, causing the loss of one or more amino acids of proteins. A number of in-frame deletion variants in an epilepsy-associated gene SCN1A, encoding voltage gated sodium channel alpha unit 1.1 (Nav1.1), have been reported in public database. In contrast to missense and truncation variants, the in-frame deletions in SCN1A remains largely uncharacterized. Methods: We summarized the basic information of forty-four SCN1A in-frame deletion variants and performed further analysis on six variants identified in our cases with epilepsy. Mutants of the six in-frame deletions and one truncating variant used as comparison were generated and co-transfected with beta-1 and -2 subunits in tsA201 cells, followed by patch clamp recordings. Results: Reviewing all the in-frame deletions showed that they spread over the entire Nav1.1 protein, without obvious “hot spots”. The dominant type (54%) was single residue loss. There was no obvious relationship between the length or locations of deletions and clinical phenotypes. The six in-frame deletions were two single residue deletions (p.M400del, p.I1772del), one microdeletion (p.S128_F130del) and three macrodeletions (p.T303_R322del, p.T160_Y202del, p.V1335_V1428del). They scatter and affect different functional domains, including transmembrane helices, pore region, and P-loop. Electrophysiological recordings revealed no measurable sodium current in all of the six mutants. In contrast, the truncating mutant p.M1619Ifs*7 that loses a long stretch of peptides retains partial function. Significance: The complete loss-of-function in these shortened, abnormal mutants indicates that Nav1.1 protein is a highly accurate structure, and many of the residues have no redundancy to ion conductance. In-frame deletion variants are potentially more deleterious to protein functions possibly due to the disruption of ordered residues.